Abstracts Accepted for Publication 2017
DOI: 10.1136/annrheumdis-2017-eular.3407
|View full text |Cite
|
Sign up to set email alerts
|

AB0812 Differentiated approach to the treatment of osteoarthritis with comorbidities

Abstract: BackgroundA significant prevalence of osteoarthritis (OA), the most disability joint disease in the world, which is important in the search for the new treatment. Analysis of modern therapy of OA was the reason for research efficacy of NSAIDs and SYSADOA on biochemical, inflammatory and immunological signs in the treatment of OA.ObjectivesDifferentiated approach to the treatment of OA depending of presence of hyperuricemia.Methods176 patients (144 women, 32 men) was exanimated, aged (59,71±0,86) years with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Various factors, such as age, cartilage metabolism, endocrine conditions, bone and joint strain, high pressure in the joint capsule, immune factors, and genetic susceptibility, may be involved in the onset of OA. 5 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various factors, such as age, cartilage metabolism, endocrine conditions, bone and joint strain, high pressure in the joint capsule, immune factors, and genetic susceptibility, may be involved in the onset of OA. 5 …”
Section: Introductionmentioning
confidence: 99%
“…The expression of vascular endothelial growth factor (VEGF) is increased in the articular cartilage of animals used to model OA. 5 A previous study assessed mRNA and protein expression of VEGF, and expression of the long non-coding RNA (lncRNA) maternally expressed gene 3 (MEG3), in cartilage samples obtained from OA patients and healthy individuals. The results of that study showed that MEG3 lncRNA is negatively correlated with that of VEGF, suggesting that MEG3 may be involved in the development of OA via regulation of angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the combination of AH and OW is considered as the most aggressive in the context of mortality, which is associated with the earlier development of target organ damage and attackable by cardiovascular catastrophes [8].…”
mentioning
confidence: 99%